Unlocking the Potential of Fishery Waste: Acid-Soluble Ultrasound Extraction of Marine Collagen from Sardine Fish Scales - Afaf Moufaddel; Khalid Bougrin; Hanae El Monfalouti; Badr Eddine Kartah (Chemistry Proceedings)
Globally, fish consumption generates significant waste from fish markets and processing industries, including fish skin, scales, and bones. If not appropriately managed, this fishery waste can lead to environmental pollution. Collagen, the most abundant protein in animal bodies, has diverse medical, biomedical, and pharmaceutical applications, but its high cost has constrained its usage. Collagen derived from marine sources, particularly from the by-products of fish processing, is seen as an alternative to collagens from land animals. There has been growing interest in utilizing fish scales as a cost-effective source of this valuable collagen-rich protein. Repurposing fish scales could alleviate environmental pressure and create additional commercial value. In a recent study, collagen was isolated from the scales of Moroccan Sardina pilchardus, a fish species renowned for its high collagen content. This marine collagen type I features a triple alpha-helical structure comprising one α2 chain and two α1 chains. The collagen extraction was accomplished using the acid-soluble collagen (ASC) method combined with an ultrasound technique after pretreating the fish scales, involving a demineralization step to remove a high amount of minerals. The ASC extracted from the sardine scales exhibited high solubility in the highly acidic pH range (pH 2). Various physicochemical techniques, such as FTIR, DRX, and SEM, confirmed the isolated protein as collagen. Hence, sardine scales could serve as an alternative source of collagen, and the characteristics of the collagens were minimally affected by the extraction process employed.